2017
DOI: 10.1007/s12298-017-0421-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression patterns of the NAC transcription factor family in Medicago truncatula

Abstract: NAC transcription factor (TF) family proteins are expressed in various developmental stages and following various stresses. NAC TFs are involved in mediating various physiological functions of plants and participate in various signaling pathways under biotic or abiotic stress. The present study provided a comprehensive functional analysis of members of the MtNAC TF family. Via screening of Medicago truncatula genome information, we identified 97 MtNAC TFs in M. truncatula and compared the phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…This approach has revealed functions to NAC proteins in several plants, such those implied in salt stress in Cucumis melo [ 62 ], drought responses in maize [ 63 ], abiotic stresses and stress-related phytohormone treatments in Brachypodium distachyon [ 64 ] and ethylene-responsive signaling in banana [ 22 ]. Other studies have assigned a wider range of functions to the NAC proteins using the same approach [ 52 , 65 , 66 , 67 , 68 ]. Thus, we run a Clustal Omega alignment with all NAC protein sequences from Arabidopsis along the six developmental and ripening related NAC TFs from strawberry to predict their functions.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has revealed functions to NAC proteins in several plants, such those implied in salt stress in Cucumis melo [ 62 ], drought responses in maize [ 63 ], abiotic stresses and stress-related phytohormone treatments in Brachypodium distachyon [ 64 ] and ethylene-responsive signaling in banana [ 22 ]. Other studies have assigned a wider range of functions to the NAC proteins using the same approach [ 52 , 65 , 66 , 67 , 68 ]. Thus, we run a Clustal Omega alignment with all NAC protein sequences from Arabidopsis along the six developmental and ripening related NAC TFs from strawberry to predict their functions.…”
Section: Resultsmentioning
confidence: 99%
“…These numbers are relatively similar to those previously reported in these species. Previously, 105 (Ooka et al, 2003) and 117 (Nuruzzaman et al, 2010) NAC genes were identified in Arabidopsis, 288 (Pereira-Santana et al, 2015) and 163 (Hu et al, 2010) in poplar, 189 in eucalyptus (Hussey et al, 2015), 97 in barrel medic (Ling et al, 2017), 124 (Fan et al, 2014) and 152 (Shiriga et al, 2014) in maize, 147 in foxtail millet (Puranik et al, 2013), 151 (Nuruzzaman et al, 2010) and 140 (Fang et al, 2008) in rice, 107 (You et al, 2015) and 118 (Zhu et al, 2015) in brome and 131 (Sanjari et al, 2019) and 145 (Kadier et al, 2017) in sorghum.…”
Section: Phylogenetic Analyses Of the Nac Transcription Factor Familymentioning
confidence: 99%
“…For this, a total of 107, 139, and 209 NAC protein sequences were used for chickpea, pigeonpea, and groundnut, respectively, including 43 well-known stress-responsive NACs from model and crop plants (Arabidopsis thaliana, Oryza sativa, Medicago truncatula and Glycine max). As most of the ANACs [45,46,47], ONACs [34,48,49], MtNACs [50], and GmNACs [41] included in the phylogenetic analysis have known functions in stress responses, 22, 31, and 33 abiotic stress-responsive NAC genes in chickpea, pigeonpea, and groundnut, respectively, were identi ed in the present study. There could be more stress-responsive NACs, dispersed on different branches if more stress-responsive NAC proteins from model plants and crops (ANAC, ONAC, MtNAC, and GmNAC) were used -as demonstrated in soybean [44].…”
Section: Discussionmentioning
confidence: 99%
“…There could be more stress-responsive NACs, dispersed on different branches if more stress-responsive NAC proteins from model plants and crops (ANAC, ONAC, MtNAC, and GmNAC) were used -as demonstrated in soybean [44]. Considering this tree-based approach, the possible role of Ca_16946 and Cc_38151 in cold-and drought stress response has been predicted as they are clustered into one subgroup with Medtr8g094580.1 [50]. Similarly, Gm_NAC066, Ca_12660, and Cc_01304 clustered into the same subgroup; Gm_NAC065 and Cc_29871 in one group; Cc_48539 and LOC_Os03g60080.1 in one subclass indicate that these genes may be involved in drought stress response [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation